1982
DOI: 10.1007/bf01249280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of domperidone on apomorphine-induced growth hormone secretion in normal men

Abstract: Domperidone, a peripheral dopamine (DA) receptor blocker which poorly crosses the blood-brain barrier and which is inactive towards dopamine-sensitive adenylate cyclase, in a dose (100 micrograms/kg) sufficient to increase serum prolactin levels at least 5-fold, decreased the growth hormone (GH) response to the DA receptor agonist, apomorphine HCI (Apo) (0.5 gm s.c.) in each of six normal men examined. The mean GH increment at 30, 45, 60 and 75 min following Apo injection, the mean individual peak increment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…7). We have found that pramipexole, like other D 2 dopamine receptor agonists (Lal et al, 1975;Müller et al, 1991; for review see Müller et al, 1999), increased GH secretion in agreement with a previous report (pramipexole : Schilling et al, 1992). It is believed that the GH release-promoting effect of the dopaminomimetic drugs is due primarily to a reduction in the release of SS (Vance et al, 1987;Giustina and Veldhuis, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…7). We have found that pramipexole, like other D 2 dopamine receptor agonists (Lal et al, 1975;Müller et al, 1991; for review see Müller et al, 1999), increased GH secretion in agreement with a previous report (pramipexole : Schilling et al, 1992). It is believed that the GH release-promoting effect of the dopaminomimetic drugs is due primarily to a reduction in the release of SS (Vance et al, 1987;Giustina and Veldhuis, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…This APO-induced penile erection and yawning was shown to be inhibited by central dopamine receptor antagonists such as sulpiride, 16 haloperidol 17 and metoclopramide, 18 but not by peripheral dopamine receptor antagonists such as domperidone which cannot pass the blood ± brain barrier. 19,20 These ®ndings would suggest that APO-induced penile erection is mediated by central mechanisms that involves activation of dopamine receptors. One site of central action of APO is believed to be the paraventricular nucleus of the hypothalamus, since APO-induced penile erection is abolished in the presence of paraventricular nucleus lesions 21 while direct administration of APO into the paraventricular nucleus causes penile erection.…”
Section: Discussionmentioning
confidence: 99%
“…The present studies in man suggest that CCK-33 has no effect on basal GH or PRL secretion. Apo increases GH secretion by an effect on a DA receptor within the hypothalamic-pituitary axis which is not linked to adenylate cyclase and which lies outside the blood brain barrier (Lal, Nair, Iskandar, Etienne, Wood, Schwartz and Guyda 1982). The DA receptor modulating PRL secretion is also located outside the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%